Demystified …: Adhesion molecule deficiencies. Issue 1 (1st February 2001) - Inwald, D; Davies, E G; Klein, N
Abstract : The basic physiology of leucocyte emigration from the intravascular space into the tissues is now known to be dependent on a class of cell surface molecules that have come to be known as adhesion molecules. Many cell–cell interactions are dependent on adhesion and signal transduction via the various adhesion molecules, particularly the integrins. The study of the functions of these molecules has been enhanced by the development of blocking and activating monoclonal antibodies, knockout mice, and by the rare "experiments of nature" in the human population, in whom there is absence or dysfunction of one of the adhesion molecules. This review describes these leucocyte adhesion defects and discusses how they have provided important insights into the function of these molecules.